Toxicity of Substances Isolated from Simarouba versicolor St. Hil. (Simaroubaceae) to the Leaf-cutting Ant Atta sexdens L. (Hymenoptera: Formicidae) and the Symbiotic Fungus Leucoagaricus gongylophorus (Singer) Möller - Peñaflor, Maria Fernanda G. V.; Almeida, Roberta N. A.; Simote, Simone Y.; Yamane, Erica; Bueno, Odair C.; Hebling, Maria J. A.; Fernandes, João B.; Vieira, Paulo C.; Silva, Maria F. G. F. da; Pagnocca, Fernando C. (BioAssay, 2009)
Leaf-cutting ants' control by means of insecticide application can cause harmful effects to the environment, non-target insect populations and human health. Vegetal products toxic to insects may represent an alternative way for controlling economically important insects for the reason that they may be more selective, besides a less residual effect. In order of this, the aim of the current study was to evaluate the toxicity of crude extracts, fractions and isolated substances from Simarouba versicolor St. Hil. (Simaroubaceae) to Atta sexdens L. (Hymenoptera: Formicidae) workers and its symbiotic fungus, Leucoagaricus gongylophorus (Singer) Möller. Leaf-cutting ants' toxicity was determined by ingestion bioassays, while the activity against the symbiotic fungus was evaluated by its development in a culture medium containing vegetal extracts. Dichloromethane fractions derived from S. versicolor methanol crude extracts showed biological activity to leaf-cutting ants and its symbiotic fungus. From these fractions, two alkaloids were isolated, 4,5-dimethoxycanthin-6-one and 5-methoxycanthin-6-one, being the first toxic only to the symbiotic fungus and the other to fungus and the ant. Purified triterpenoids from others S. versicolor extracts didn’t show deleterious effect to both leaf-cuttings ants and the symbiotic fungus.